A recent progress of room–temperature airborne ozone decomposition catalysts - Ma, Jiami; Cao, Ranran; Dang, Yanliu; Wang, Jinlong (Chinese chemical letters, 2021)
This review presents recent advances of O3 decomposition catalysts and provides fundamental understandings of active sites and corresponding deactivation mechanism, which is helpful for the design of new O3 decomposition catalysts. [Display omitted] Ozone (O3) plays essential roles in stratosphere and helps reduce the amount of harmful ultraviolet arriving the Earth’s surface. However, O3 is also a strong oxidant and causes troubles to human health in troposphere, especially in the confined space, such as indoor environment. Recently, O3 abatement materials have become research hotspots due to the urgent environmental demands. Catalysis is a facile strategy that can eliminate indoor airborne O3 efficiently and economically. Thus, this review summarizes the recent progresses of O3 decomposition catalysts. The catalysts covered here are categorized as follows: zeolite, metal organic frameworks (MOFs), metal oxides, noble metals. Manganese–based catalysts display higher efficiency and are mainly discussed. Generally, the active sites of O3 decomposition catalysts are described as Lewis acid sites (e.g., zeolite), metal sites (e.g., MOFs), oxygen vacancy sites (e.g., MnO2) in the previous work. In this review, we ascribe all the active sites to unsaturated metal sites and their Lewis acidity. Possible evidence from the experimental and theoretical perspectives are proposed. Furthermore, the strategy to circumvent deactivation caused by peroxides (O22–) accumulation and water molecular competition are also elaborated. Finally, perspective is presented on the challenges and opportunities of exploring existing and new O3 decomposition catalysts.